Genome-wide association study reveals heat tolerance QTL for canopy-closure and early flowering in chickpea - Jeffrey, Cara; Kaiser, Brent; Trethowan, Richard; Ziems, Laura (Frontiers in Plant Science, 2024)
Chickpeas are a vital source of protein and starch for a large portion of the world's population and are known to be impacted by heat stress at every life stage. Previously known as an "Orphan Legume", little is known of the genetic control of heat stress tolerance, and most previous research has focused on heat avoidance rather than tolerance. This study utilised a population of 148 chickpea genotypes, primarily Kabulis, in 12 field trials conducted at 2 locations, two sowing periods, and across 3 years. Physiology was examined, and data was paired with Diversity Arrays Technology (DArT) sequencing to perform a Genome Wide Association Study to connect phenotypic and genotypic regions. Fourteen QTL related to yield, seed size, time to flowering, time to maturity, and final canopy closure were found. Among these, are the first Quantitative Trait Loci (QTL) ever identified for canopy closure in chickpea, along with a QTL that is likely linked to early flowering under heat stress. Early flowering in this case refers to a cultivar flowering significantly earlier than the others in the genotype set. Additionally, several other QTL provide validation of previous research. These QTL hotspots that can be targeted for selective breeding of several traits concurrently. Overall, new targets for genome assisted breeding for heat tolerance in chickpea were identified and can be utilised by the breeder community to improve the status of selective breeding for heat tolerance in this crop.